Peran Tata Kelola Perusahaan Dalam Respon Investor Atas Penerapan Nilai Wajar Properti Investasi Dan Aset Tetap di Indonesia - Much. Rizal P. Geno; Amrie Firmansyah (Owner : Riset dan Jurnal Akuntansi, 2022)
Investors consider the good firm value of the company in the hope of providing additional wealth in the future. Company information announced to the public provides a signal for investors regarding company policies. Fair value accounting provides more timely and transparent information to investors to assess the financial position and the entity performance if it refers to the prevailing values. This study examines the association of applying fair value to investment properties and fixed assets with firm value. This research method employs a quantitative approach. In addition, this study examines the role of corporate governance in the relationship between the application of the fair value of investment properties and fixed assets with firm value. The research data sources from the financial statements of property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) are from www.idx.co.id. Moreover, stock price information is sourced from www.finance.yahoo.com from 2016 to 2019. Based on purposive sampling, the total sample of this study amounted to 52 observations. This study indicates that the implementation of fair value to investment properties is positively associated with firm value, while the application of fair value to fixed assets is negatively associated with firm value. Meanwhile, corporate governance cannot moderate the positive effect of implementing the fair value of investment properties and fixed assets with firm value. This research indicates that the Financial Services Authority needs to improve its corporate governance policies and monitor the implementation of corporate governance applied to companies listed on the IDX.